FLY ASH AND SILICA FUME SUBSTITUTION ON COMPRESSIVE STRENGTH AND PERMEABILITY OF CONCRETE IN THE MARINE ENVIRONMENT - Ignatius Sudarsono; S. Imam Wahyudi; Henny Pratiwi Adi (LPPM Universitas Negeri Jakarta, 2023)
Cement, as a concrete-forming material, is a contributor to CO2 emissions in the world. Reducing cement and substituting fly ash and silica fume as concrete substitution materials in the manufacture of concrete makes green concrete without lowering the quality of the concrete. Concrete in the marine environment is frequently destroyed by severe environmental elements, such as seawater penetration; hence, high-performance concrete materials are required. This research aims to analyze the effect of adding fly ash and silica fume on concrete compressive strength and permeability. The specimens made were then immersed in freshwater and seawater. Analysis of the compressive strength test result shows that the compressive strength values ​​for the samples treated with freshwater or seawater have exceeded the expected compressive strength of 30 MPa. The permeability test on the test object resulted in the supplementary fly ash to the concrete immersed in freshwater having a good value, i.e., the water penetration was below that required by DIN-1045, namely 5 cm. The penetration of concrete with fly ash impressed in seawater is good only in concrete with a 10% fly ash variation. The water penetration value still meets the requirements in concrete with silica fume for all variations with freshwater and seawater treatment.